Factors influencing intention to plagiarize among nursing students in the Philippines - Mary Bless G. Debuque; John Bernard A. Dofitas; Dorothy Arlene Paz P. Espia; Trixie Camille R. Ferrariz; Francis John P. Gargarita; Ryan Michael F. Oducado (Belitung Raya Foundation, Indonesia, 2023)
Background: Plagiarism is an ethical concern among students but is insufficiently discussed and acknowledged in some educational institutions. Determining what factors influence plagiarism can help the academic community manage its incidence. Objective: This study determined the factors affecting the intention to plagiarize among Filipino nursing students. Methods: Utilizing a cross-sectional research design, data were gathered from 304 nursing students last June 2021 using valid instruments administered online. Regression analysis identified influencing factors of intention to plagiarize. Results: Findings indicated a generally low intention (M = 1.47, SD = 0.74) to plagiarize among nursing students. Internet literacy (B = -0.314, p <0.001), attitude (B = 0.257, p <0.001), moral obligation (B = -0.236, p <0.001), past behavior (B = 0.139, p <0.001), and subjective norm (B = -0.095, p = -0.001) influenced nursing students’ plagiarism intention. Conclusion: Several interrelated factors play major roles in nursing students’ tendency to plagiarize. Creating an educational environment that does not favor the unethical practice of plagiarism is recommended for nursing schools.